Clinical experience with heparin-containing eye ointment for dry eye - D.M. Safonova; A.O. Root; V.D. Yartsev; M.N. Narbut (РМЖ "Клиническая офтальмология")
D.M. Safonova, A.O. Root, V.D. Yartsev, M.N. Narbut Scientific Research Institute of Eye Diseases, Moscow, Russian Federation Currently, the development and evaluation of the efficacy of combined agents for dry eye is an important issue. This paper summarizes authors’ clinical experience with heparin-containing eye ointment for dry eye. Aim: to assess clinical efficacy of eye ointment with heparin for dry eye. Patients and Methods: non-controlled prospective clinical study included 21 patients (41 eyes) with moderate scleral conjunctival xerosis. Mean age was 73±8 years. All patients received PARIN-POS® (Ursapharm, Germany) eye ointment with heparin. At baseline and after 4 weeks of the treatment, lacrimal meniscometry was performed to measure lower tear meniscus depth; in addition, Ocular Surface Disease Index (OSDI) score was calculated in 10 patients. Statistical analysis was performed using Wilcoxon test. Difference was considered statistically significant at p less than 0.05. SOFA Statistics 1.4.4 software (Paton-Simpson and Associates, New Zealand) was applied to perform statistical data analysis. Results: at baseline and after 4 weeks of the treatment, lower tear meniscus depth and OSDI score were significantly different. Tear meniscus depth was 75 to 310 μm (median 150 μm) at baseline and 81 to 338 μm (median 201 μm) after 4 weeks of the treatment. OSDI score was  13 to 19 (median 15) at baseline and 6 to 15 (median 9) after 4 weeks of the treatment. Conclusion: PARIN-POS® eye ointment with heparin demonstrated clinical efficacy in dry eye patients PARIN-POS® increases tear film thickness and decreases ocular discomfort. Key words: dry eye syndrome, corneal conjunctival xerosis, heparin, PARIN-POS, OSDI, tear meniscus, tear film. For citation: Safonova D.M., Root A.O., Yartsev V.D., Narbut M.N. Clinical experience with heparin-containing eye ointment for dry eye. Russian Journal of Clinical Ophthalmology. 2019;19(1):2–5. About the authors: Daria M. Safonova — MD, PhD, Junior Research Associate of the Modern Methods of Treatment in Ophthalmology; Anna O. Root — MD, PhD, ophthalmologist; Vasily D. Yartsev — MD, PhD, Research Associate of the Lacrimal Pathology Department; Maria N. Narbut — Junior Research Associate of the Refractive Changes Department. Scientific Research Institute of Eye Diseases. 11a, Rossolimo st., Moscow, 119021, Russian Federation. Contact information: Vasily D. Yartsev, e-mail: v.yartsev@niigb.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 11.12.2018.